Analisis Bahasa Kiasan Ironi dalam Lirik Lagu Album Blurryface - Erna Pranata Putri; Indah Mustika Santhi (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This research aims to describe the use of ironic figurative language in popular song lyrics. The research used descriptive qualitative, with data consisting of excerpts from song lyrics. The data source is the Blurryface album by the American band Twenty-One Pilots. This research applies Perrine’s theory of figures of speech as the analytical framework. The findings showed that there are two cases of situational irony, one case of dramatic irony, and one case of verbal irony. The study concludes that the use of irony in song lyrics functions to strengthen meaning, evoke listeners’ emotions, and serve as a medium for social criticism and self-reflection.